A Randomized Comparative Study of Luteolin-Based Herbal Unani Formulations versus Nitrofurantoin in Women with Uncomplicated Urinary Tract Infections - Sultana, Arshiya; Rahman, Khaleequr; Alam, Saiyad Shah (Current Pharmaceutical Design, 2025)
BackgroundUrinary tract infection (UTI) is a common infection, particularly among reproductive-age and elderly women. While antibiotics remain the primary treatment, antimicrobial resistance is a growing global concern, necessitating effective non-antibiotic alternatives.ObjectivesThis study determines the safety and efficacy of herbal formulation compared to nitrofurantoin in treating uncomplicated UTI and its impact on health-related quality of life (HRQoL) in women.MethodologyA randomized, standard-controlled study was conducted involving 66 women diagnosed with uUTI. Participants were randomly assigned to either the Unani Herbal Formulations group (UHF) or the nitrofurantoin group (NG). The UHF group (n=33) received a Unani herbal formulation (3.5 g powder of Cucumis sativus L., Lagenaria siceraria, Portulaca oleracea L., Malva sylvestris L., and Adiantum capillus-veneris L.) along with 25 ml of Viola odorata L. syrup, administered twice daily for 8 days. The NG (n=33) received nitrofurantoin (100 mg) twice daily for 7 days. The primary outcome was the Urinary Tract Infection Symptom Assessment (UTISA) questionnaire. The secondary outcomes were symptom severity, urine dipstick test, urine culture and sensitivity, SF-12 HRQoL survey, and safety evaluation. Standardization, in vitro, and phytochemical analyses of the herbal formulation were also conducted.ResultsUTISA scores significantly improved within both groups (p < 0.001). The UTISA total score from 14.21 ± 3.43 and 14.18 ± 3.36 was reduced to 3.12 ± 4.65 and 1.61 ± 3.10 in the UHF and NG, respectively, on the 9th day. On the 9th day, 81.81% (UHF) and 87.87% (NG) had negative cultures. HRQoL scores showed significant within-group improvements (p < 0.001), with no significant difference between groups (p > 0.05). No adverse effects were reported. HPLC analysis confirmed the presence of Luteolin, a bioactive antimicrobial metabolite.ConclusionThe herbal formulations were as effective as nitrofurantoin in treating bacterial uUTIs, with no adverse effects and enhanced HRQoL. The presence of Luteolin supports its antimicrobial potential, offering a favourable non-antibiotic alternative for UTI management.Trial RegistrationThe research project is registered at the Clinical Trial Registry of India, ICMR with No: CTRI/2021/09/036138 dated 01/09/2021. The protocol can be retrieved from CTRI.
Keywords: nitrofurantoin